1997
DOI: 10.1111/j.1439-0396.1997.tb00864.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cell walls, dry matter and protein supply on endogenous nitrogen flow in the small intestine of sheep

Abstract: Summary Five sheep, fitted with a PVC cannula in the dorsal rumen, a silastic infusion tube in the abomasum, and a single T‐shape PVC cannula in the proximal duodenum (D1), distal duodenum (D2), mid‐jejunum (J) and terminal ileum (I), were fed diets, which varied in crude protein (N × 6.25) and fibre contents. A 15N labelled grass meal‐beer yeast suspension was continuously infused into the abomasum over a period of 1 week. Subsequently, over a period of 4 days, the 15N excess in D1, D2, J and I digesta was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…Recently experiments of Voigt et al (1996) and Van Bruchem et al (1997) using intra-abosomal 15 N infusion to multifistulated sheep resulted in an average of 3.1 g endogenous N at the proximal duodenum, which is 12% of the total N flux at the duodenum and corresponds to 2.8 g/kg DM intake. Lammers-Wienhoven et al (1998) who used the same method estimated a higher value: 4.3 g endogenous N, equivalent to 15% of total N flux at the duodenum or 4.2 g/kg DM intake. Brandt et al (1980) estimated, by the use of intraruminal 15 N infusion, similar values in dairy cows (3.6 g endogenous protein N/kg DM passage at the proximal duodenum or 9-12% of NAN flow).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Recently experiments of Voigt et al (1996) and Van Bruchem et al (1997) using intra-abosomal 15 N infusion to multifistulated sheep resulted in an average of 3.1 g endogenous N at the proximal duodenum, which is 12% of the total N flux at the duodenum and corresponds to 2.8 g/kg DM intake. Lammers-Wienhoven et al (1998) who used the same method estimated a higher value: 4.3 g endogenous N, equivalent to 15% of total N flux at the duodenum or 4.2 g/kg DM intake. Brandt et al (1980) estimated, by the use of intraruminal 15 N infusion, similar values in dairy cows (3.6 g endogenous protein N/kg DM passage at the proximal duodenum or 9-12% of NAN flow).…”
Section: Discussionmentioning
confidence: 97%
“…This higher CF content gives rise to enhanced sloughing of epithelial cells and therefore to a higher endogenous NAN flux into the duodenum. Recently, Lammers- Wienhoven et al (1998) demonstrated in sheep that the flow of endogenous N into the duodenum increased from 20 to 28%) of total N flow if the dietary NDF content was increased from 15 to 68%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors found average values of 50%). In the studies of Lammers-Wienhoven et al (1998) the N reabsorbility amounted to 56%. These differences are likely due to the mode of calculation.…”
Section: Discussionmentioning
confidence: 93%
“…Thus the net N secretion into the rumen and the abomasum could be calculated using the quotient of 15 N enrichment in the duodenal digesta and the TCE soluble blood plasma of the animal No. 2 (Lammers-Wienhoven et al, 1998). The N secreted by bile and the pancreatic fluid (Sandek et al, 2001a) was subtracted from this value.…”
Section: Calculation Of N Secretion N Secretion In Stomachsmentioning
confidence: 99%